Accuracy of proposers' beliefs in an allocation-type game - Federica Alberti; Anna Conte; Kei Tsutsui (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
In the context of an allocation game, this paper analyses the proposers reported beliefs about the responders willingness to accept (or reject) the proposed split of the pie. The proposers beliefs are elicited via a quadratic scoring rule. An econometric model of the proposers beliefs is estimated. The estimated proposers beliefs are then compared with the actual responders choices. As a result of this comparison, we observe that the proposer tends to underestimate the empirical acceptance probability, especially when the slice of the pie allocated to the proposer is large.
Keywords: C51; C52; C72; D84; 330; allocation game; beliefs elicitation and evaluation; model construction and estimation